2006
DOI: 10.1093/ajcn/83.6.1526s
|View full text |Cite
|
Sign up to set email alerts
|

n−3 Fatty acid dietary recommendations and food sources to achieve essentiality and cardiovascular benefits

Abstract: Dietary recommendations have been made for n-3 fatty acids, including alpha-linolenic acid (ALA), eicosapentaenoic acid (EPA), and docosahexaenoic acid (DHA) to achieve nutrient adequacy and to prevent and treat cardiovascular disease. These recommendations are based on a large body of evidence from epidemiologic and controlled clinical studies. The n-3 fatty acid recommendation to achieve nutritional adequacy, defined as the amount necessary to prevent deficiency symptoms, is 0.6-1.2% of energy for ALA; up to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
367
4
9

Year Published

2007
2007
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 524 publications
(387 citation statements)
references
References 67 publications
7
367
4
9
Order By: Relevance
“…Nevertheless, it is generally accepted that the ratio of n-6 to n-3 in Western diets (20-30:1) is less than optimal and should be improved to approach recommendations (4-5:1) (57) . As expected, the present study showed a gradual decrease of the n-6:n-3 ratio in participants with a better adherence to the MD.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, it is generally accepted that the ratio of n-6 to n-3 in Western diets (20-30:1) is less than optimal and should be improved to approach recommendations (4-5:1) (57) . As expected, the present study showed a gradual decrease of the n-6:n-3 ratio in participants with a better adherence to the MD.…”
Section: Discussionmentioning
confidence: 99%
“…Molecular mechanisms are less well understood but include effects on hepatic lipid metabolism such as decreasing TAG synthesis, that involve, among other mechanisms, the important role of PUFA in transcriptional regulation of genes of lipid metabolism (Deckelbaum et al, 2006;Georgiadi and Kersten, 2012). Based on their effects on CVD, many health agencies worldwide recommend up to 500 mg/d of EPA and DHA for reducing CVD risk or 1 g/d for secondary prevention in existing CVD patients, with a dietary strategy for achieving 500 mg/d being to consume 2 fish meals per week with at least one of oily fish (ISSFAL, 2004;Gebauer et al, 2006;Aranceta and Perez-Rodrigo, 2012).…”
Section: Cardiac and Cardiovascular Disease (Cvd)mentioning
confidence: 99%
“…The percent of fat as ALA in flaxseed is 5.5 times higher than that in the next-highest sources, walnuts, and canola oil (GEBAUER et al, 2006). According to Hettiarachchy et al (1990), flaxseed contains 32-45% of oil, of which 51-55% is α-linolenic acid (n-3 fatty acid) and 15-18% is linoleic acid.…”
Section: Chemical Composition Of Flaxseedmentioning
confidence: 99%